Anodic Stripping Determination of Pt (IV) Based on the Anodic Oxidation of Cu from the Intermetallic Phase of Cu[3]Pt; Procedia Chemistry; Vol. 10 : Chemistry and Chemical Engineering in XXI century - Ustinova E. M. Elvira Maratovna (2014, 2014)
Title screen